Real human touch: performer-facilitated touch enhances presence and embodiment in immersive performance - Desnoyers-Stewart, John; Bergamo Meneghini, Margherita; Stepanova, Ekaterina R.; Riecke, Bernhard E. (Frontiers in Virtual Reality, 2024)
Despite being an embodied medium, Virtual Reality (VR) prioritizes vision and sound over the other senses. While touch has been demonstrated to foster a sense of presence and embodiment, most haptic research in VR focuses on uncanny vibration motors or limited experiences of touch with simple props. Meanwhile, immersive performances such as Eve 3.0 incorporate performerfacilitated touch in novel ways to evoke a complete and social experience of human touch in VR. In response, we conducted a mixed-methods study to investigate the experience of performer-facilitated touch in a 360°video segment from the immersive performance Eve 3.0.Using a 3x2 factorial design we compared touch from a diary prop and performer and festival and lab settings. We found that performer-facilitated touch increased realistic behaviours and questionnaire measures of social presence, embodiment, and tactile realism. The setting also had a significant effect with festival participants demonstrating significantly more behaviours indicating presence, particularly in the no-touch condition. Participant descriptions reveal that in addition to touch, a rich narrative and vivid visuals of social interaction were just as important in immersing participants in the experience and making them feel present. We find that participant experiences are a co-creation situated at the intersection of the artefact and context that require a willing suspension of disbelief. The authentic setting and performance artefact afforded a deep understanding of the rich and complex experience of human touch in immersive performance.